Pendekatan Metodologi Dalam Penelitian Metabolisme Pada Ruminansia - Djokowoerjo Sastradipradja (Media Veteriner, 1997)
Climatic factor of high temperatures and humidities of humid tropical countries, alongside with the occmence of diseases and parasites have created a complex situation in terms of the effect on animal production. Studies on quantitative relationships for better understanding of digestion, metabolism and related areas are lacking. There are however a number of appropriate methodologies available for conducting onfarm metabolic research aiming at giving better understanding of animal production and health in the humid tropics. The paper discusses methodologies and experimental approaches developed in the authors's laboratory on growing,draft pregnant and lactating ruminants. Several examples of the results are presented.